FORMATION AND USE OF HORSE MILITARI DETEACHMENTS BY IMAM SHAMIL' (1834-1859) - Dadaev, Usup Usmanovic; Dadaev, Kamil' Sulejmanovic (History, Archeology and Ethnography of the Caucasus, 2016)
The article is devoted to the formation and use of military units in the cavalry during the Imamate of the Caucasian War. Based on the analysis of primary sources and archival materials in the article shows the process of forming the cavalry, its size, perform combat missions and participated in the battles. The authors cite the names of many heroes of the Caucasian war, directly involved in the formation and organization of the state Imamate equestrian military orders/
Keywords: Imamate of Shamil; Daghestan; Caucasus war; the formation of the cavalry